Introduction chapter of traditional and article-based theses: a comparison of rhetorical structures and linguistic realisations - Abdolmalaki, Shahrbanou Ghorban; Tan, Helen; Abdullah, Ain Nadzimah; Sharmini, Sharon (Universiti Kebangsaan Malaysia Press, 2019)
Article-based thesis is an alternative thesis format which requires postgraduate students to write and publish articles as a fulfilment of a postgraduate degree. Therefore, knowledge of the rhetorical structure (moves and steps) of article-based thesis (AT) is crucial for the successful completion of a thesis. This study then seeks to compare the rhetorical structures and linguistic realisations of thesis introduction chapter found in the Traditional (TT) and Article-based (AT) theses. To realise the objectives, 12 purposive selected PhD thesis introductions were analysed based on Bunton’s (2002) move model. Using content analysis, the moves and steps in the introduction chapters were quantified for their frequency of use and then examined qualitatively for their linguistic realisations. The data revealed that both types of theses had obligatory and optional moves and steps. It was also found that the steps of move 3 in the article-based theses were slightly different from that in the traditional theses. For the linguistic realisations, it was shown that there were variations in the different moves and steps in TT and AT. Words such as paper and article were found in move 3 in AT but were absent in TT. The results have several pedagogical implications. They provide informed input on the structures of the two types of thesis to the writing instructors and writing curriculum writers. More importantly, the findings provide knowledge to student writers on the genre of AT, specifically its rhetorical structures and linguistic realisations.